Do educated women in Sierra Leone support discontinuation of female genital mutilation/cutting? Evidence from the 2013 Demographic and Health Survey - Ameyaw, Edward K; Yaya, Sanni; Seidu, Abdul-Aziz; Ahinkorah, Bright O; Baatiema, Linus; Njue, Carolyne (Université d'Ottawa | University of Ottawa, 2020)
Abstract Introduction Female genital mutilation/cutting (FGM/C) comprises all procedures that involve the total or partial elimination of the external genitalia or any injury to the female genital organ for non-medical purposes. More than 200 million females have undergone the procedure globally, with a prevalence of 89.6% in Sierra Leone. Education is acknowledged as a fundamental strategy to end FGM/C. This study aims to assess women's educational attainment and how this impacts their views on whether FGM/C should be discontinued in Sierra Leone. Methods We used data from the 2013 Sierra Leone Demographic and Health Survey. A total of 15,228 women were included in the study. We carried out a descriptive analysis, followed by Binary Logistic Regression analyses. We presented the results of the Binary Logistic Regression as Crude Odds Ratios (COR) and Adjusted Odds Ratios (AOR) with 95% confidence intervals (CIs). Results Most of the women with formal education (65.5%) and 15.6% of those without formal education indicated that FGM/C should be discontinued. Similarly, 35% of those aged 15–19 indicated that FGM/C should be discontinued. Women with a higher education level had a higher likelihood of reporting that FGM/C should be discontinued [AOR 4.02; CI 3.00–5.41]. Christian women [AOR 1.72; CI 1.44–2.04], those who reported that FGM/C is not required by religion [AOR 8.68; CI 7.29–10.34], wealthier women [AOR 1.37; CI 1.03–1.83] and those residing in the western part of Sierra Leone [AOR 1.61; CI 1.16–2.23] were more likely to state that FGM/C should be discontinued. In contrast, women in union [AOR 0.75; CI 0.62–0.91], circumcised women [AOR 0.41; CI 0.33–0.52], residents of the northern region [AOR 0.63; CI 0.46–0.85] and women aged 45–49 [AOR 0.66; CI 0.48–0.89] were less likely to report that FGM/C should be discontinued in Sierra Leone. Conclusion This study supports the argument that education is crucial to end FGM/C. Age, religion and religious support for FGM/C, marital status, wealth status, region, place of residence, mothers' experience of FGM/C and having a daughter at home are key influences on the discontinuation of FGM/C in Sierra Leone. The study demonstrates the need to pay critical attention to uneducated women, older women and women who have been circumcised to help Sierra Leone end FGM/C and increase its prospects of achieving Sustainable Development Goals (SDG) three and five.